Pengaruh Overconfidence dan Herding behavior terhadap Keputusan Investasi Saham dengan Literasi Keuangan sebagai Variabel Mediasi pada Investor Generasi Muda Pengguna Aplikasi Stockbit di Kota Palangka Raya - Meiggi Putra; Solikah Nurwati; Violly Yuzico; Afriardi Budiari Pratama; Jessica Septiana Harto (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study examines the effects of overconfidence, herding behavior, and financial literacy on stock investment decisions and tests the mediating role of financial literacy among young Stockbit investors in Palangka Raya City. Using an explanatory quantitative design, data were collected through a five-point Likert-scale online questionnaire with purposive sampling. Of 137 responses, 120 valid responses were analyzed using PLS-SEM with SmartPLS 4. The results show that overconfidence (O=0.289; p=0.000), herding behavior (O=0.183; p=0.008), and financial literacy (O=0.524; p=0.000) positively and significantly affect stock investment decisions. However, overconfidence (O=0.099; p=0.285) and herding behavior (O=0.029; p=0.790) do not significantly affect financial literacy. Their indirect effects are also insignificant. Therefore, financial literacy does not mediate either relationship. The model explains 42.3% of stock investment decisions and 1.1% of financial literacy.